2007
DOI: 10.1242/dev.005967
|View full text |Cite
|
Sign up to set email alerts
|

BMP signalling inhibits premature neural differentiation in the mouse embryo

Abstract: The specification of a subset of epiblast cells to acquire a neural fate constitutes the first step in the generation of the nervous system. Little is known about the signals required for neural induction in the mouse. We have analysed the role of BMP signalling in this process. We demonstrate that prior to gastrulation, Bmp2/4 signalling via Bmpr1a maintains epiblast pluripotency and prevents precocious neural differentiation of this tissue, at least in part by maintaining Nodal signalling. We find that durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
163
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(179 citation statements)
references
References 78 publications
14
163
2
Order By: Relevance
“…The inhibition of BMP signaling seems revolutionarily conserved during the neural fate initiation in different organisms (9,13,52). Inhibition of the TGF␤ pathway has now been demonstrated to be sufficient to directly induce neural fate in mammalian embryos as well as pluripotent mouse and human embryonic stem cells (53), and consistently, our data also showed that the TGF␤ signaling has been inhibited during hESC neural differentiation processing (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…The inhibition of BMP signaling seems revolutionarily conserved during the neural fate initiation in different organisms (9,13,52). Inhibition of the TGF␤ pathway has now been demonstrated to be sufficient to directly induce neural fate in mammalian embryos as well as pluripotent mouse and human embryonic stem cells (53), and consistently, our data also showed that the TGF␤ signaling has been inhibited during hESC neural differentiation processing (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…These models have been questioned, based mostly on observations in the mouse system, in which signaling through BMP receptors appears to be required only for mesoderm induction and not for trophoblast lineage specification (23,46). The identification of BMP4-inducible p63, which is dispensable for mouse placentation (47), as an early marker of human proliferative CTB, may explain why BMP4 induces the TE lineage in hPSCs but appears not to be required for the same process in mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that AP2γ is concurrently regulated by other signals, such as FGF and Wnt [74]. BMP is proved to inhibit prematuration of neural tissues in the mouse embryo [12]. AP2γ might be the executor of BMP signaling in the nucleus to guarantee the normal progress of neural development by suppressing excessive cSox2 expansion in the young neural plate.…”
Section: Discussionmentioning
confidence: 99%
“…The "default model" proposes that BMP inhibits the "default" neural tendency of the ectodermal cells and induces them to adopt an epidermal fate, while BMP antagonists (noggin, chordin, and follistatin) from the organizer inhibit BMP signaling to protect the default neural fate [7,10,11]. The study in mouse embryo indicates that BMP signaling is required for inhibiting premature neural differentiation [12], and the involvement of Fgf and Wnt signaling pathways in neural induction has been established by the evidence from Xenopus and chick embryo [1,2,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%